2021
DOI: 10.31557/apjcc.2021.6.3.243-247
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Middle Euphrates Region of Iraq: Risk Factors, Presenting Symptoms and Time to Medical Help-Seeking

Abstract: Background: Breast cancer is the most frequently occurring tumor and the first cause of death in females. Low level of understanding early symptoms leads to a late diagnosis and high mortality rates. Aims: To describe presenting symptoms, risk factors, and medical care delays among breast cancer patients in Iraq. Materials & Methods: A retrospective, descriptive study conducted in Al-Hussein center in Karbala province of Iraq between February 2012 and August 2020.Results: There were 101 female patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The sample sizes of the studies ranged from 10 to 499 for the quantitative, qualitative, and mixed studies. The studies were conducted across 10 countries in Asia: 18 studies are from South Asia [ 23 , 24 , 29 – 31 , 33 , 34 , 37 – 39 , 41 48 ], seven studies are from Southeast Asia [ 25 28 , 32 , 36 , 40 ], and a study from Western Asia [ 35 ] (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample sizes of the studies ranged from 10 to 499 for the quantitative, qualitative, and mixed studies. The studies were conducted across 10 countries in Asia: 18 studies are from South Asia [ 23 , 24 , 29 – 31 , 33 , 34 , 37 – 39 , 41 48 ], seven studies are from Southeast Asia [ 25 28 , 32 , 36 , 40 ], and a study from Western Asia [ 35 ] (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies identified health workforce. Among the health workforce factors, the unavailability of doctors [ 32 , 35 ], especially oncologists and cancer specialists [ 38 , 48 ] served as a barrier to early diagnosis and treatment of breast cancer. Several studies reported the lack and preference for female doctors over male doctors [ 24 , 31 , 37 – 39 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the serum level of irisin was positively correlated with tumor stage. These results suggest that irisin can be used in the early diagnosis, differential diagnosis, and prognosis of breast cancer (13)(14)(15)(16) .…”
Section: Discussionmentioning
confidence: 94%
“…This retrospective descriptive research was carried out in the Al-Hussein Cancer Center in Karbala province of Iraq on female breast cancer patients diagnosed between January 2012 and August 2020. Our center covers not only Karbala peoples but other patients from the Middle Euphrates area in Iraq who are referred to this center for solid and hematological malignancy management [9]. All patients were diagnosed by tru-cut or excisional biopsy and confirmed by immunohistochemistry markers.…”
Section: Study Design and Participantsmentioning
confidence: 99%